An unprecedented and large-scale support mission to assist residential care facilities during the COVID-19 pandemic - Anaïs Colas; Alexandre Baudet; Marie Regad; Elodie Conrath; Muriel Colombo; Arnaud Florentin (Elsevier, 2022)
Summary: Background: In March 2020, COVID-19 cases occurred in residential care facilities. To assist these facilities, the regional health agency of the Meurthe-et-Moselle administrative district ordered a support mission. Methods: Infection prevention and control mobile teams were formed under the coordination of the infection prevention and control department (IPCD) of a university hospital. Teams went to residential care facilities for the elderly, to facilities for people with disabilities (FPD) and independent living communities (ILC). They visited the facilities and met with the management and the ward staff to assess the situation and to identify any potential support needs. Results: Over two non-consecutive weeks, 104 residential care facilities were visited (9025 residents). If urgent needs were identified, the IPCD was directly informed by the teams to initiate an extensive assistance operation. Thereby, additional staff and equipment were provided for every facility in need. Although most of them had implemented good management to face the pandemic, four emergency field support operations took place in facilities with uncontrolled outbreaks. Conclusions: This is the first reported support action for residential care facilities during the pandemic in France. As no major outbreaks were noticed later, this mission was deemed a success and met the residential care facilities' needs for support. Many facilities have expressed the need to cooperate with infection prevention and control specialists in the future, both during outbreaks, also in routine daily practice. This report highlights the need to maintain support for residential care facilities and to implement a permanent collaboration between hospitals and residential care facilities.